The Seventies Sociality: Activist Publishers and the Digital Commonplacing of New Knowledge - Crompton, Constance; Voth, Caitlin; Truong, Ruth (KULA, 2019)
The historiography of gay liberation publishing offers much to the digital humanities, especially if read through Peter Stallybrass’ argument that ‘reading is a technology of inventorying information to make it reusable.’ He suggests ‘commonplacing’ to make clear that every individual’s thoughts are informed by others’ voices. This paper asks how we might best go about this commonplacing work using linked data, building on the DIY practices of gay liberationists.